MAKNA TEKS DALAM KUMPULAN SAJAK CAHAYA MAHA CAHAYA KARYA EMHA AINUN NADJIB (KAJIAN HERMENEUTIK WILHELM DILTHEY) - Heriyani, Ida Trisna; Juanda, Juanda; Hajrah, Hajrah (Fakultas Bahasa dan Sastra Indoensia, 2020)
The general purpose of this research is to describe the concept of Erlebnis (life Experience), Ausdruck (expression), and Verstehen (understanding) contained in the poetry collection of the Cahaya Maha Cahaya by Emha Ainun Nadjib. The approach used in this study was the hermeneutics approach of Wilhelm Dilthey. Data is collected using the Read and note method. The results of this study show some concepts: (1) The Erlebnis concept that says that the background of poetry is very influential with the experiences of its creators. (2) The Ausdruck concept suggests that Emha wanted to reveal about a human being whose search for the nature of life was against his lord. (3) The concept of Verstehen shows the relationship between the meaning of poetry and real life.